Clinical characteristic of esophageal cancer without lugol‐voiding lesions in the background esophagus. Issue 4 (20th March 2020) - Kuwabara, Hiroki; Chiba, Hideyuki; Tachikawa, Jun; Okada, Naoya; Ashikari, Keiichi; Arimoto, Jun; Nakaoka, Michiko; Sakai, Eiji; Goto, Toru; Ohata, Ken
Abstract : Lugol chromoendoscopy is useful for the detection of early esophageal squamous cell cancer (ESCC). Multiple lugol‐voiding lesions (LVLs) on lugol chromoendoscopy are associated with a very high risk of multiple cancers arising in the esophagus. Due to the widespread use of narrow band image technology in many institutions, esophageal cancer without LVLs in the background esophagus is sometimes detected. This retrospective study aims to clarify the clinical characteristic of esophageal cancer without LVLs in the background esophagus. A total of 191 consecutive patients with 204 ESCCs had undergone endoscopic submucosal dissection (ESD) from 2011 and 2014. Amongst these lesions, the number of LVLs in the background esophagus per endoscopic view was counted excluding main lesion, and the grading was divided into no LVLs ESCC (nL‐ESCC) group and LVLs ESCC (L‐ESCC) group. This study evaluated the clinical characteristics and the cumulative incidence of metachronous ESCC after ESD in both groups. Thirty‐six patients with 36 lesions and 155 patients with 168 lesions were separated into the nL‐ESCC group and L‐ESCC group, respectively. On multivariate analysis, the nL‐ESCC group was found to be more common in females, who were non‐drinkers, or with erosive esophagitis. During follow‐up periods, the cumulative incidence of metachronous ESCC at 3‐years was 14.4% and 0.00% in the L‐ESCC and nL‐ESCC groups, respectively ( P  < 0.01). Our study showed that esophageal cancer without LVLs in the background esophagus was mostly occurred in females, who were non‐drinkers, or with erosive esophagitis, which are uncommon features of ESCC.